A novel surgical margin (1 cm) might be from benefit for patients with dysplastic nevi, thin melanomas, and melanoma in situ: Analysis based on clinical cases. Issue 2 (17th February 2020) - Tchernev, Georgi; Malev, Valeri; Patterson, James W.; Lotti, Torello
Abstract: Malignant melanoma is an oncologic disease, whose current management among others includes surgical and immunological therapy. According to the current recommendations of the American Joint Committee on Cancer, the surgical excision of the primary tumor should be performed in two operative sessions, which has several consequences. The following paper will present and discuss six cases of pigmented lesions and the advantages of the one‐step melanoma surgery in their management.